Юридична відповідальність за правопорушення в природоохоронній сфері: теоретико-методологічні проблеми - Бойчук, А. Ю.; Boichuk, Andrii (Одеса : Гельветика, 2018)
Статтю присвячено розкриттю теоретичних та методологічних основ формування та розвитку юридичної відповідальності за порушення у природоохоронній сфері. Поняття юридичної відповідальності за равопорушення в природоохоронній сфері пройшло тривалий шлях становлення та розвитку, який супроводжувався низкою методологічних проблем. Дослідження проблеми юридичної відповідальності та її динаміки за різних історичних часів є одним із найбільш актуальних та складних питань сучасної юридичної науки і практики. Аналіз правотворчих процесів переконливо доводить та свідчить, що суспільство та особа не можуть існувати без захисту від правопорушень та осіб, що їх вчиняють, а отже, без нормативно-правових актів, в яких закріплено юридичну відповідальність за вчинення конкретних правопорушень. The article is devoted to the disclosure of theoretical and methodological foundations of the formation and development of legal liability for violations in the environmental sphere. The concept of legal responsibility for offenses in the environmental sphere has been a long way to becoming and development and was accompanied by a number of methodological problems. The study of the problem of legal liability and its dynamics in different historical times is one of the most urgent and complex issues of modern legal science and practice. The analysis of law-making processes convincingly proves and shows that society and the individual can not exist without protection from offenses and those who carry them out, and therefore, without normative legal acts, which impose legal responsibility for the implementation of specific offenses. First, such liability is based on the norms of Soviet law, it is formally determined, detailed, and has a general binding character. Secondly, it is guaranteed by the Soviet state, connected with the exclusive state property on natural resources and with the state-power activity of bodies of Soviet power. Thirdly, it is provided by compulsion or state persuasion, the activities of public organizations, aimed at propaganda, preservation of certain natural objects. Fourth, the consequences of legal liability are condemnation and punishment, in some cases, state approval, support and encouragement. Fifthly, it is carried out in accordance with the procedure established by the Soviet legislation.
Бойчук А. Ю. Юридична відповідальність за правопорушення в природоохоронній сфері: теоретико-методологічні проблеми / А. Ю. Бойчук // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2018. - № 5. – C. 126 - 140.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; юридична відповідальність; природоохоронна сфера; земельне законодавство; юридическая ответственность; правонарушения; природоохранная сфера; земельное законодательство; legal responsibility; environmental sphere; land legislation